Characteristics of carbonaceous aerosols in large-scale Asian wintertime outflows at Cape Hedo, Okinawa, Japan. (October 2016) - Shimada, K.; Takami, A.; Kato, S.; Kajii, Y.; Hasegawa, S.; Fushimi, A.; Shimizu, A.; Sugimoto, N.; Chan, C.K.; Kim, Y.P.; Lin, N.H.; Hatakeyama, S.
Abstract: We have performed long-term measurements of organic carbon (OC) and elemental carbon (EC) in atmospheric aerosols at Cape Hedo Atmosphere and Aerosol Monitoring Station (CHAAMS). Large-scale East Asian continental outflows of aerosols have frequently been observed at CHAAMS in both winter and spring, but large-scale air pollution (LSP) events in winter have not yet been described in the literature. Examination of PM2.5 in LSP events showed that it consisted mainly of carbonaceous aerosols and sulfate. We compared OC and EC concentrations measured at CHAAMS during LSP events with those measured at the same time in East Asian cities, and with concentrations measured at CHAAMS during an Asian dust event in spring 2006. The maximum OC and EC concentrations at Cape Hedo during LSP events were comparable to those at China Atmosphere Watch Network sites in China. The average OC concentration was also similar to concentrations measured at urban sites in Taipei (Taiwan), Seoul (Korea), and Tokyo (Japan); EC, however, was several times lower at Cape Hedo than EC concentrations at these urban sites. We identified three types of air masses associated with LSP events: Type 1, a polluted air mass composed of freshly emitted pollutants; Type 2, an air mass that underwent photochemical aging during transport from China to Okinawa; and Type 3, an air mass that was almost fully aged in China before being transported to Japan. Simulations of LSP events with a 3-D chemical transport model (Chemical Weather Forecasting System) indicated that Type 1 air masses were associated with "cone type" transport in a low-pressure system, and Type 2 air masses were associated with "giant puff type" transport by a migratory high-pressure system. Generally speaking, air pollutants are transported from China to CHAAMS in winter in association with the north or northwest monsoon. High levels of air pollutants in China in winter are due to higher emissions and poorer dispersion because of the low boundary layer height and low wind speeds. Our results suggest that LSP events occur when a cold front forms under accumulated air pollutants. The mass contribution of carbonaceous materials to PM2.5 during the LSP event in winter 2008 was 36%, much larger than the contribution of 19% during the spring 2006 dust event. Highlights: Large-scale East Asian outflows of aerosols were frequently observed in winter. The OC concentration was similar to concentrations measured at urban sites in Asia. The EC concentration was several times lower than concentrations at urban sites in Asia. An OC/EC analysis suggested large-scale outflows are caused by air masses containing freshly or aged pollutants. The simulation model showed that large-scale outflows were associated with "giant puff type" clouds covering most of Japan.